Inhibitory Effects of Jiuzao Polysaccharides on Alcoholic Fatty Liver Formation in Zebrafish Larvae and Their Regulatory Impact on Intestinal Microbiota - Qing Li; Liling Wu; Guangnan Wang; Fuping Zheng; Jinyuan Sun; Yuhang Zhang; Zexia Li; Lianghao Li; Baoguo Sun (Foods, 2024)
The liver is critical in alcohol metabolism, and excessive consumption heightens the risk of hepatic damage, potentially escalating to hepatitis and cirrhosis. Jiuzao, a by-product of Baijiu production, contains a rich concentration of naturally active polysaccharides known for their antioxidative properties. This study investigated the influence of Laowuzeng Jiuzao polysaccharide (LJP) on the development of ethanol-induced alcoholic fatty liver. Zebrafish larvae served as the model organisms for examining the LJPs hepatic impact via liver phenotypic and biochemical assays. Additionally, this study evaluated the LJPs effects on gene expression associated with alcoholic fatty liver and the composition of the intestinal microbiota through transcriptomic and 16 S rRNA gene sequencing analyses, respectively. Our findings revealed that LJP markedly mitigated morphological liver damage and reduced oxidative stress and lipid peroxidation in larvae. Transcriptome data indicated that LJP ameliorated hepatic fat accumulation and liver injury by enhancing gene expression involved in alcohol and lipid metabolism. Furthermore, LJP modulated the development of alcoholic fatty liver by altering the prevalence of intestinal Actinobacteriota and Firmicutes, specifically augmenting Acinetobacter while diminishing Chryseobacterium levels. Ultimately, LJP mitigated alcohol-induced hepatic injury by modulating gene expression related to ethanol metabolism, lipid metabolism, and inflammation and by orchestrating alterations in the intestinal microbiota.